Evaluate the Performance of Some Oat (Avena sativa L.) Genotypes Responsibility to Different Nitrogen Fertilization Treatments (Journal of Hama University, 2020)
The study was carried out in Abi Jarash Farm, Faculty of Agriculture, Damascus University, during the growing season 2018-2019; to determine the response of nine oats genotypes to different nitrogen fertilization treatments (control: without N fertilization, 100, 150 and 200 kg ha-1) based on some morphological and yield associated traits. The experiment was conduct according to split randomized complete block design (Split-RCBD) with three replications for each treatment and genotype, such as: number of plants per square meter, plant length, number of productive tillers, grain numbers per plant, 1000- kerenel weight, grain yield and harvest index. The results of statistical analysis showed that the treatment 200 kg.ha-1 was superior in all studied traits. The variety Tajikstan  was superior in plant length (131.67 cm), number of productive tillers (3.00 tiller.plant-1), grain numbers per plant (122.18 kerenel.plant-1) and grain yield (765.00 g.m-2); while the results indicated that the variety Mexico was superior in number of plants per square meter (333.3 plant.m-2) and harvest index (42.39%). It was also noticed that the variety Romania943 was superior in 1000- kerenel weight (30.95 g).